2019
DOI: 10.4103/joacp.joacp_104_18
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine with propofol versus fentanyl with propofol for insertion of Proseal laryngeal mask airway: A randomized, double-blinded clinical trial

Abstract: Background and Aims:Successful insertion of the proseal laryngeal mask airway (PLMA) requires much greater doses of propofol as compared to classic laryngeal mask (CLMA). Dexmedetomidine and fentanyl are equally effective adjuvants for CLMA insertion. We designed this study to compare the efficacy of these two drugs as sole adjuvant in PLMA insertion.Material and Methods:Seventy four American Society of Anesthesiologists (ASA) I and II patients were randomly allocated to receive either dexmedetomidine 1 μg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…But when compared between the groups (Group F & Group D ) it was statistically significant at 30 sec, 1 min, 2min interval after the induction and insertion of LMA (p=0.034). These findings are comparable with the previous studies [16][17][18][19].…”
Section: Discussionsupporting
confidence: 93%
“…But when compared between the groups (Group F & Group D ) it was statistically significant at 30 sec, 1 min, 2min interval after the induction and insertion of LMA (p=0.034). These findings are comparable with the previous studies [16][17][18][19].…”
Section: Discussionsupporting
confidence: 93%
“…Effective rate of LMA catheterization Five articles (8,10,11,12,14), comprising a total of 300 patients, reported the effective rate of laryngeal canal.…”
Section: Analysis Resultsmentioning
confidence: 99%
“…Hill et al (19) found that intravenous fentanyl had a stronger effect on respiratory depression than other anesthetic drugs. In this meta-analysis, 3 articles (8,10,11) reported on changes in the respiratory rate of patients 1 min to 15 min after LM catheterization, and all 3 studies used fentanyl sedation in the control group. During anesthesia induction, the respiratory rate of patients in the control group was lower than that of patients in the dexmedetomidine group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations